William Carlos Williams and the Ethics of Painting - Diggory, Terence, 1951- (Book collections on Project MUSE., 1991)
In Peter Brueghel's painting The Adoration of the Kings, the depiction of Joseph and Mary suggested to William Carlos Williams a paradigm for the relationship between poem and painting, reader and text, man and woman, that he had sought throughout his life to establish: a marriage that can acknowledge and withstand infidelity. Here Terence Diggory explores the meaning of this paradigm within the context of Williams's career and also of recent critical and cultural debate, which frequently assumes violence and oppression to be inherent in all forms of relationship. Williams's special attention to the art of painting, Diggory shows, put him in a position to challenge such assumptions. In contrast to the "ethics of reading" deduced by J. Hillis Miller from the premises of deconstruction, Diggory illuminates Williams's "ethics of painting" by applying Julia Kristeva's concepts of psychoanalytic transference and nonoppressive desire. The abstract or "objectless" space in which such desire operates is typified by modernist painting, for both Kristeva and Williams, but foreshadowed in the work of earlier artists such as Bellini and Brueghel. Originally published in 1991. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905